Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1152/japplphysiol.00734.2015
|View full text |Cite
|
Sign up to set email alerts
|

Mild loss of lung aeration augments stretch in healthy lung regions

Abstract: Inspiratory stretch by mechanical ventilation worsens lung injury. However, it is not clear whether and how the ventilator damages lungs in the absence of preexisting injury. We hypothesized that subtle loss of lung aeration during general anesthesia regionally augments ventilation and distension of ventilated air spaces. In eight supine anesthetized and intubated rats, hyperpolarized gas MRI was performed after a recruitment maneuver following 1 h of volume-controlled ventilation with zero positive end-expira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 63 publications
(74 reference statements)
0
17
0
Order By: Relevance
“…The acquisition scheme was closely related to three previously published imaging methods (9)(10)(11). Each of these methods has been shown to be useful in diagnosis or staging of COPD, detecting early changes in asymptomatic smokers, or to provide a meaningful imaging surrogate for specific clinical lung function tests (12)(13)(14)(15). The technique presented here also contains a computational technique for deriving oxygen uptake by the capillary blood in a manner that is much less sensitive to imaging noise than those previously explored (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition scheme was closely related to three previously published imaging methods (9)(10)(11). Each of these methods has been shown to be useful in diagnosis or staging of COPD, detecting early changes in asymptomatic smokers, or to provide a meaningful imaging surrogate for specific clinical lung function tests (12)(13)(14)(15). The technique presented here also contains a computational technique for deriving oxygen uptake by the capillary blood in a manner that is much less sensitive to imaging noise than those previously explored (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…in the adjacent patent alveoli and that alveolar size actually decreases with increased airway pressure (i.e., PEEP) if lung tissue is recruited by a mechanism of gas redistribution (Cereda et al, 2011(Cereda et al, , 2013(Cereda et al, , 2016a. It has also been shown that gas redistribution in the microenvironment is not only pressure dependent but also time dependent (i.e., the longer the pressure is applied, the better the gas redistribution) (Figure 7) (Kollisch-Singule et al, 2014b).…”
Section: Ventilating Within the Constraints Of An Acutely Injured Lungmentioning
confidence: 99%
“…Even with low Vt, tissue injury may occur regionally, since overdistension is not global but occurs in the microenvironment. Specifically, alveolar and alveolar duct overdistension occurs in open tissue surrounding a collapsed area of stress-focus or adjacent to areas of alveolar instability (Figures 4, 6, 7) (Mead et al, 1970;Cereda et al, 2011Cereda et al, , 2013Cereda et al, , 2016aKollisch-Singule et al, 2014b, 2018Makiyama et al, 2014;Nieman et al, 2017b;Ruhl et al, 2019). Indeed, it has been shown that atelectasis, not high Vt, causes overdistension FIGURE 7 | Rat lungs fixed at inspiration and expiration in normal lungs (Control) and in a Tween lavage ARDS model with four ventilation strategies:…”
Section: Ventilating Within the Constraints Of An Acutely Injured Lungmentioning
confidence: 99%
“…In a murine model of surfactant depletion, atelectasis was found to occur primarily in dependent regions of the lung but demonstrated that ventilator induced injury occurred in the non-dependent/non-atelectatic regions (Tsuchida et al, 2006), likely because tidal volumes were distributed to the regions of increased compliance (Gattinoni and Pesenti, 2005). Another murine study of healthy lungs mechanically ventilated with Vt 10 mL•kg −1 and ZEEP plus recruitment maneuvers used CT and MRI imaging to determine regional lung variations in response to mechanical ventilation (Cereda et al, 2016a). Ventilation with ZEEP led to heterogeneity of and an increase in regional fractional ventilation as measured by MRI, yet did not demonstrate macroscopic atelectasis on CT scan (Cereda et al, 2016a).…”
Section: Alveolar Heterogeneitymentioning
confidence: 99%
“…Another murine study of healthy lungs mechanically ventilated with Vt 10 mL•kg −1 and ZEEP plus recruitment maneuvers used CT and MRI imaging to determine regional lung variations in response to mechanical ventilation (Cereda et al, 2016a). Ventilation with ZEEP led to heterogeneity of and an increase in regional fractional ventilation as measured by MRI, yet did not demonstrate macroscopic atelectasis on CT scan (Cereda et al, 2016a). This study demonstrated both the heterogeneous effect mechanical ventilation may have on the lung and also that subtle alterations in the micro-environment may not manifest on a macro-scale (Cereda et al, 2016a).…”
Section: Alveolar Heterogeneitymentioning
confidence: 99%